Effects of the Inlet Velocity Profiles on the Prediction of Velocity Distribution inside an Electrostatic Precipitator (ESP) - Ahmad Fitri, Yusop; R., Mamat; Mohd Hafizil, Mat Yasin; Shafiq, Suhaimi (IACSIT Press, 2014)
In this study, the development of CFD model for the description of operation of electrostatic precipitator has been developed. The model is based on the simulation analysis whereby focused on the gas flow by time-averaged conservation equation of mass and momentum. 2D geometry model was extensively applied due to ease the geometry and analysis. The flow simulation was performed by using computational fluid dynamics (CFD) code Fluent. Numerical calculations for the air flow were calculated using the Reynolds-averaged Navier-Stokes equation coupled with the realizable k-ε turbulence model equations. Simulations were performed using three velocities at the inlet boundary by considering a uniform (ideal) velocity profile. Simulation with the low velocity profile gives a better flow rate efficiency between the outlet and inlet of the ESP. Overall, all the three velocities give more than 90% of efficiency of the air flow inside ESP chamber.